Pengaruh Model Pembelajaran Snowball Throwing Terhadap Motivasi Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas VIII SMP Negeri 1 Sipoholon Tahun Pembelajaran 2023/2024 - Vhillia Novi Rostanti Purba; Wilson Simanjuntak; Taripar Aripin Samosir; Malani Simanungkalit; Dame Taruli (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
The aim of this research is to determine the difference in learning motivation of students who are taught using the snowball throwing learning model and those who are not taught using the Snowball Throwing learning model at SMP Negeri 1 Sipoholon for the 2023/2024 academic year. The method used in this research is a quantitative research method with a pre-experimental design research type in the form of a one-group-pretest-posttest design. The population was all class VIII students at SMP Negeri 1 Sipoholon, totaling 188 people and the researchers determined a sample of 32 people using a purposive sampling technique. Data was collected using a positive closed questionnaire with 27 items. Research data for the questionnaire was analyzed using the related sample formula. From the calculation results, the tcount value = -29.052<ttable 2.039 with a 2-party test (α/2=0.05/2=0.025)= 2.039. The tcount value is in the curve area of ​​rejection of H0 and acceptance of H1. Thus, it can be concluded that the research hypothesis is accepted, namely that there is a difference in the learning motivation of students who are taught using the snowball throwing learning model and those who are not taught using the Snowball Throwing learning model at SMP Negeri 1 Sipoholon for the 2023/2024 academic year. The difference in learning motivation for Christian Religious Education and Characteristics of Class VIII Students at SMP Negeri 1 Sipoholon for the 2023/2024 Academic Year can be seen from the average scores of X1 = 77.0 and X2 = 88.3.